"Love Hurts": Romantic Attachment and Depressive Symptoms in Pregnant Adolescent and Young Adult Couples. Issue 1 (21st June 2013) - Desrosiers, Alethea; Sipsma, Heather; Callands, Tamora; Hansen, Nathan; Divney, Anna; Magriples, Urania; Kershaw, Trace
<x xml:space="preserve">Abstract</x> Objective The current study investigates the relationship between romantic attachment style and depressive symptoms between both members of pregnant adolescent and young adult couples. Method Participants were 296 pregnant young females (mean age = 18.7) and their male partners (mean age = 21.3; 592 total participants) who were recruited from obstetrics and gynecology clinics in Connecticut. The dimensions of avoidant and anxious romantic attachment were assessed using the Experiences in Close Relationships Inventory. Depressive symptoms were measured using the Center for Epidemiological Studies‐Depression Scale. Results Results showed that avoidant attachment and anxious attachment were significantly positively related to depressive symptoms. Multilevel modeling for partner effects revealed that anxious attachment and depressive symptoms in partners were significantly positively associated with depressive symptoms Conclusion Findings underscore the importance of considering couples‐based approaches to supporting the transition to parenthood and developing the necessary self and relationship skills to manage attachment needs and relationship challenges.